Exploring the Relevance of Knowledge-Based Networking (Social Media) Tools Among Family Businesses - Nóra Obermayer (International School for Social and Business Studies, 2018)
Behind the success of an organization can be found the ability to manage the constantly 'renewing' knowledge effectively. Knowledge sharing is a vital part of knowledge management. The recent remarkable growth in Internet-based business activities has proved that many different advantages can be derived from communication technology platforms. Internet has changed the way people communicate, collaborate, learn and conduct business. It has delivered to organizations a global market presence, and online marketing has become an essential part of business. Both organizations and customers are more and more involved in social media. Different knowledge-based (social) networking tools have experienced significant growth in recent years. In 2014, an exploratory survey investigated how social media tools were being used for knowledge sharing and whether their usage was supported by Hungarian organizations. As a continuation, a new research focuses on leading family businesses, as their economic and societal value creation is extremely important in the country. The aims of the research are to explore the relevance and usage of knowledge-based networking tools to ascertain the benefits and challenges, as well as to define the reasons and purposes of using social media technologies. In this research, qualitative methodology was used to collect data through semi-structured interviews in 2018. The results indicate that social media provides a great opportunity to reach potential customers. It was found that the most popular social media tools are Facebook, LinkedIn and Instagram. The findings also show that enterprises face some challenges, such as how to respond to customers in real-time.